The nonlinear dynamic buckling behaviour of imperfect solar cells subjected to impact load. (December 2021) - Li, Qingya; Tian, Yuhang; Wu, Di; Gao, Wei; Yu, Yuguo; Chen, Xiaojun; Yang, Chengwei
Abstract: Solar cells are becoming a strong competitor in the new energy market due to their superior ability to generate electricity in an environmentally friendly and sustainable manner. The present study is devoted to presenting a theoretical framework for nonlinear dynamic buckling behaviours of imperfect multilayer solar cells subjected to impact loading resting on the elastic foundation. Two types of solar cell models, namely, organic solar cell (OSC) and perovskite solar cell (PSC), with simply supported and clamped boundary conditions are investigated. Sinusoidal, exponential, rectangular, and damping pulse functions are considered Based on the first-order shear deformation plate theory, the nonlinearity are introduced with the aid of von Kármán theory. The equations of the dynamic system of the plate with the consideration of large-deflection are derived by the Galerkin method and then solved by the fourth-order Runge–Kutta methods. After validation, some parametric experiments are performed to explore the influences of the pulse duration, pulse function pulse amplitude, initial imperfection, boundary conditions, Winkler–Pasternak​ elastic foundation coefficients, and damping ratios on the dynamic stability of the structures. Highlights: Nonlinear dynamic buckling analysis of solar cells is studied. Sinusoidal, exponential, rectangular, and damping pulse functions are considered. The organic and perovskite solar cells are under investigation. Geometric imperfection, elastic foundation, and damping effects are examined. Simply supported and clamped boundary conditions are studied.